Деякі проблемні моменти етногенезу українців та його завершальний етап - Балушок, В. (Народна творчість та етнографія, 2005)
In the 12th century two "integrating centers" at the territory of Ukraine had intensified their integrating activity - the Haluch-Volynian and Chernigiv and joined their efforts in struggling for the Kyiv principate. Thus, the new ethno-political unity was formed. The Northern and the North-Eastern lands of Rus had separated themselves from Êyiv establiching their own ethno-political unions. The appearance of the separate ethno-political union at the territory of the South Rus resulted in the formation of the common South-Russian communication systems, including the information system; and common South-Russian ethnoces elite had emerged. This, in its turn, had led to the formulation and common usage of such ethnonym as "Rus" (plural) /"Rusin" (singular) as a self-name at the end of the 12th and the beginning of the 13th centuries. The appearance of the unified name for the whole South Russian lands at the end of the 12th and the beginning of the 13th century witnessed to the fact that the ethnic formation process was nearing completion at that time. The ethnonym was in use as the self-name of all Ukrainians up to the first half of 18th century, and probably later.